PENGENALAN ISO 31OOO: INTERNATIONAL RISK MANAGEMENT STANDARDS - Rosita Widjojo (Center for Economic Studies Universitas Katolik Parahyangan, 2008)
Risk management is becoming an important issue in companies. Therefore, the ISO recognized the need to establish a standard for risk management, which is still in the process of approval from all ISO members, and will be published by the end of 2008 or early 2009 after a consensus has been reached. ISO standards provide requirements or give guidance on good management practice. ISO 31000 for international Risk Management Standards is considered as a generic management system standard, which means that the same standard can be applied to any organization, large or small, whatever its product or service, in any sector of activity, and whether it is a business enterprise, a public administration, or a government department. The objective of this article focuses on the introduction of ISO 31000 and the framework, to give a brief description of how risk management can be applied in organizations. Organizations with a commitment to managing risk know that implementing standards can enable them to do so more effectively and therefore maximize opportunities and minimize losses in the course of achieving corporate objectives.